Cost-effective treatment of uncomplicated gonorrhoea including co-infection with Chlamydia trachomatis - (:unkn) unknown (Springer International Publishing, 1997)
We evaluated the cost effectiveness of treating uncomplicated gonorrhoea in a theoretical cohort of 1,000 adults (nonpregnant women of reproductive age, or men) with either intramuscular ceftriaxone 125 mg or a single oral dose of cefixime 400 mg, ofloxacin 400 mg or ciprofloxacin 500 mg. We assumed that all patients were also empirically treated for uncomplicated chlamydial infection, with either a single oral dose of azithromycin 1g, or oral doxycycline 100 mg twice daily for 7 days. Treatment of gonorrhoea with intramuscular ceftriaxone was found to be the most cost-effective alternative. This was followed by treatment with the either of the fluoroquinolones (ofloxacin or ciprofloxacin), then cefixime. For empirical treatment of uncomplicated chlamydial infection, doxycycline was more cost effective than azithromycin when approximately more than 80% of the patients were assumed to comply with the doxycycline regimen. When patients' compliance was poor with the doxycycline regimen, the azithromycin therapy became more cost effective from a societal viewpoint. Nevertheless, its relatively high cost to the individual patient with limited financial resources might prevent him or her from filling prescriptions. Any decrease in patients' compliance with the azithromycin therapy would favour treatment with doxycycline.